METODE PEMBELAJARAN TAHSIN AL-QUR’AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DI SEKOLAH MENENGAH PERTAMA ISLAM AL-IKHLAS KOTA JAMBI - Wulandari, Tania; Marwazi; Musli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Tahsin Al-Qur’an learning method in improving students’ ability to read the Al-Qur’an at Sekolah Menengah Pertama Islam Al-Ikhlas Kota Jambi. The problem underlying this research is the variation in students’ ability to read the Al-Qur’an, particularly in pronunciation, application of tajwid rules, and reading fluency. This research uses a qualitative method with a descriptive approach. The study was conducted as field research, and the subjects consisted of the principal, Tahsin teachers, Islamic education teachers, and students. Data were collected through observation, interviews, and documentation, and analyzed descriptively to obtain an in-depth understanding of the learning process. The findings show that the implementation of the Tahsin Al-Qur’an learning method was carried out using several approaches, including the Qira’ati, Iqra’, Yanbu’a, Ummi, and Tilawati methods. Supporting factors included school policies, adequate facilities and infrastructure, and students’ motivation, while inhibiting factors included fluctuating student enthusiasm, differences in learning absorption, limited variation in teaching techniques, time constraints, lack of concentration, low self-confidence, and weak discipline. Teachers addressed these obstacles by recognizing individual student characteristics, providing constructive feedback and correction, motivating students, offering emotional support, and conducting periodic evaluations. Overall, the implementation of the Tahsin method contributed to improving students’ reading accuracy, fluency, and confidence in reading the Al-Qur’an.